Infant distress to novelty is associated with maternal anxiety disorder and especially with maternal avoidance behavior - Reck, Corinna; Müller, Mitho; Tietz, Alexandra; Möhler, Eva (Journal of anxiety disorders, 2013)
Research suggested that maternal anxiety disorders might be related to infants’ behavioral inhibition. This study investigated whether maternal postpartum anxiety disorder is associated with infant temperament, more precisely, infant distress to novelty, an early predictor of behavioral inhibition. Differences in the latter were analyzed in a German sample by comparing n=38 healthy mother-infant dyads to n=44 dyads comprised of mothers diagnosed with a DSM-IV anxiety disorders. Infant age ranged from 2.83 to 7.97 months. Infant temperament was measured by means of the Infant Behavior Questionnaire. Mothers were screened for postpartum anxiety disorder using the Structured Clinical Interview for DSM-IV Disorders. Severity of anxiety was measured by self-reported questionnaires (Anxiety Cognition Questionnaire, Body Sensations Questionnaire and Mobility Inventory). Infant salivary cortisol reaction when being confronted with a socio-emotional stressor (Face-to-Face-Still-Face paradigm) was assessed to validate infant distress. A Mann-Whitney-U analysis suggested that infants of mothers with an anxiety disorder show more distress to novelty than infants of healthy mothers. Furthermore, data reveal a positive Spearman's ρ-correlation between infant distress to novelty and maternal avoidance behavior (Mobility Inventory). A strong correlation between infant cortisol reactivity and reported distress to novelty validated the maternal evaluation of infant temperament in our sample. Results suggest a possible approach to promote infant development by encouraging mothers with anxiety symptoms to encounter feared stimuli.
Gesehen am 17.12.2021